Peran Pancasila Sebagai Dasar Hukum Nasional Dalam Penerapan Keselamatan dan Kesehatan Kerja Bagi Tenaga Kerja di Indonesia - Dewanto Jassy Santoso (PT. Hasba Edukasi Mandiri, 2025)
The increasing development of industry across various sectors is inextricably linked to the importance of Occupational Health and Safety (OHS) aspects. Negligence in Occupational Health and Safety (OHS) can lead to workplace accidents that impact not only the individual but also others. The trend of workplace accidents reflects the failure to implement OHS procedures and a lack of awareness regarding rights, obligations, and fairness in the workplace. This study aims to analyze the role of Pancasila as the legal basis for fulfilling worker’s Occupational Health and Safety (OHS) rights through a literature approach. The method used is analytical and normative library research, examining various relevant scientific sources such as journals, publications, official documents, and laws and regulations that discuss the role of Pancasila, Occupational Health and Safety (OHS), and occupational accident insurance. The results of this study indicate that Pancasila serves as the legal basis for laws and regulations related to the implementation of Occupational Health and Safety (OHS). These laws and regulations aim to uphold worker’s dignity and create fairness in the workplace. Implementing Pancasila values in every Occupational Health and Safety (OHS) policy and program is a concrete way of creating a safe, healthy, fair, humane, and participatory work environment that protects worker’s dignity. Furthermore, the implementation of an occupational accident insurance program is one of the responsibilities and obligations of workplace owners and the government to provide socio-economic protection to workers.